Analisis Pengaruh Waktu Penyimpanan pada Sampel Serum untuk Pemeriksaan Kolestrol - Arisanti, Dewi; Suardi, Suardi; Lesmana, Utami Ayu; Muharram, Andi Fatmawati; Rustiah, Wa Ode; Muawanah, Muawanah (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2025)
Cholesterol testing is an important parameter for monitoring lipid metabolism disorders characterized by a decrease or increase in lipid content. The purpose of this study is to determine the effect of storage time on serum samples for cholesterol testing that is delayed by 2 hours and immediate testing. This research was conducted in the laboratory of Puskesmas Tarakan using laboratory observation with the CHOD-PAP method, with the research subjects being students of Politeknik Muhammadiyah Makassar. Based on the cholesterol examination results using 15 samples that were directly tested, there were 3 samples that showed an increase and 12 other samples had normal values. After a 2-hour delay, there was a decrease in all 15 samples. In the paired sample t-test, it can be observed that the average serum sample for direct examination is 170 mg/dl, while the serum sample delayed by 2 hours has an average value of 131 mg/dl, showing a significance of 0.01 < 0.05. Therefore, it can be concluded that there is a significant effect between the direct serum sample and the serum sample delayed by 2 hours. The storage of serum at room temperature must be done immediately to ensure more accurate results and to avoid enzyme changes in the serum.Key words: CHOD-PAP, cholesterol, direct examination.